Prenatal paternal anxiety symptoms predict child DHEA levels and internalizing symptoms during adrenarche - Jones, Sherri Lee; De Braga, Victoria; Caccese, Christina; Lew, Jimin; Elgbeili, Guillaume; Castellanos-Ryan, Natalie; Parent, Sophie; Muckle, Gina; Herba, Catherine M.; Fraser, William D.; Ducharme, Simon; Barnwell, Julia; et al. (Frontiers in Behavioral Neuroscience, 2024)
INTRODUCTION. This study examined 1) whether measures of paternal anxious and depressive symptoms collected prenatally and during a follow-up assessment when the child was in middle childhood, predict child neuroendocrine outcomes, and 2) whether neuroendocrine outcomes are intermediate factors between paternal mental health and child cognitive/behavioral outcomes. Middle childhood coincides with increased autonomy as the child transitions into grade school, and with adrenarche, as the maturing adrenal gland increases secretion of dehydroepiandrosterone (DHEA) and its sulfated metabolite (DHEA-S), hormones that are implicated in corticolimbic development which regulate emotions and cognition. METHOD. Participants were recruited from a subsample of a large prospective birth cohort study (3D Study). We conducted a follow-up study when children were 6-8 years old (N=61 families, 36 boys, 25 girls). Parental symptoms of anxiety, stress and depression were assessed via validated self-report questionnaires: prenatally using an in-house anxiety questionnaire, the Perceived Stress Scale (PSS) and the Center for Epidemiologic Studies Depression (CES-D), and at the follow up, using the Beck Anxiety and Beck Depression Inventories. Children provided salivary hormone samples, and their pituitary gland volume was measured from structural Magnetic Resonance Imaging (MRI) scans. Child behaviors were measured using the Strengths and Difficulties Questionnaire and cognitive outcomes using the WISC-V. Multiple regression analyses were used to test whether paternal mental health symptoms assessed prenatally and during childhood are associated with child neuroendocrine outcomes, adjusting for maternal mental health and child sex. Indirect-effect models assessed whether neuroendocrine factors are important intermediates that link paternal mental health and cognitive/behavioral outcomes. RESULTS. 1) Fathers' prenatal anxiety symptoms predicted lower DHEA levels in the children, but not pituitary volume. 2) Higher prenatal paternal anxiety symptoms predicted higher child internalizing symptoms via an indirect pathway of lower child DHEA. No associations were detected between paternal anxiety symptoms measured in childhood, and neuroendocrine outcomes. No child sex differences were detected on any measure. CONCLUSION. These results highlight the often-overlooked role of paternal factors during pregnancy on child development, suggesting that paternal prenatal anxiety symptoms are associated with child neuroendocrine function and in turn internalizing symptoms that manifest at least up to middle childhood.